OVERVIEW OF HISTORY THOUGHTS ON THE ESTABLISHMENT OF ISLAMIC BANKS IN INDONESIA - Kadir, Syahruddin; Ismail, Ismail; Nur, Abustan; Ihsan, Akmal; Rizal, Abd (Economic and Science Faculty of Islamic State University, 2024)
Islamic economic thought in Indonesia is not something that suddenly appears on the surface without any basis but is present because of the presence of figures who bring the concept of thought that becomes theoretical Islamic economics. This thought must be examined and found traces of historical truth. The purpose of this research focuses on the discussion of the history of Islamic economic thought in Indonesia and the history of the institutionalization of Islamic economics and Islamic banks in Indonesia. This research method is a qualitative literature study of journal articles and relevant documents. The results of this study indicate that the history of Islamic economics in Indonesia began with the entry of Islam into Indonesia and the establishment of Islamic kingdoms in the archipelago (Indonesia). Islam had spread in Sumatra in 1200 AD (597 Hijriyah). The practice of trade tax carried out by the Islamic kingdoms of the archipelago referred to what had been practiced in the kingdoms originating from the Middle East. Then trade practices began to be written in Mirât al-Thullâb by Shaykh Abdul Ra'uf al-Sinkili which became a source of Islamic economic thought. Meanwhile, the establishment of Islamic banks was a collaboration between the Indonesian Muslim Scholars Association and MUI. The participation of Indonesian President Soeharto as the initiator of the establishment of the first Sharia bank in Indonesia, as well as the personal role of several former ministers and ministers of the Development V cabinet. With a capital of Rp.116 billion, the Islamic bank began operations on 1 May 1992.